2016
DOI: 10.1111/bjep.12118
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social cognitive and personality factors on teachers' reported inclusive behaviour

Abstract: This study demonstrates the application of TPB to an educational setting and contributes to the understanding of teachers' reported use of inclusive strategies for children with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 83 publications
1
41
0
Order By: Relevance
“…RUNNING HEAD: SCHOOL ENVIRONMENT, MASTERY EXPERIENCE, EFFICACY BELIEFS AND INCLUSION Drawing on SCT, we examined whether school working environment variables (school climate perceptions and collective efficacy) and mastery experience could predict teacher self-efficacy in relation to using inclusive practise for children with ID. We focused specifically on inclusion of children with ID because previous research has found teacher self-efficacy to be an important factor in the successful inclusion of this group of learners (Wilson et al, 2016). We assessed teacher self-efficacy sub-scales (instructional strategies, classroom management and student engagement), collective efficacy, school climate perceptions and mastery experience.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…RUNNING HEAD: SCHOOL ENVIRONMENT, MASTERY EXPERIENCE, EFFICACY BELIEFS AND INCLUSION Drawing on SCT, we examined whether school working environment variables (school climate perceptions and collective efficacy) and mastery experience could predict teacher self-efficacy in relation to using inclusive practise for children with ID. We focused specifically on inclusion of children with ID because previous research has found teacher self-efficacy to be an important factor in the successful inclusion of this group of learners (Wilson et al, 2016). We assessed teacher self-efficacy sub-scales (instructional strategies, classroom management and student engagement), collective efficacy, school climate perceptions and mastery experience.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…Whilst policy mandates inclusion, it is teachers’ behaviour that determines its success. For example, attitudes towards inclusion play a key role in the use of specific inclusive teaching practices (Ahmmed, Sharma and Deppeler, ; MacFarlane and Woolfson, ; Wilson, Woolfson, Durkin, et al., ) and may impact upon readiness to embrace inclusive pedagogy (see Florian and Rouse, ; Lambe and Bones, ).…”
Section: Attitudes Towards Inclusionmentioning
confidence: 99%
“…Research has also explored the association between learning difficulties and behavior problems (Roberts et al, 2019), showing that lower academic achievement is a risk factor for developing behavior difficulties among students with special educational needs and disabilities (Oldfield et al, 2017). The study of the learning context and the school environment, which facilitates or hinders learning, has shown that the expectations from teachers and their attitudes toward children with special needs are some of the most influential elements (Anderson et al, 2014;Wilson et al, 2016;Bowles et al, 2018). Research has also found that teachers can have an important influence on the social acceptance of peers with special needs (Schwab et al, 2016), which is important because the social exclusion of children can affect their learning difficulties and behavior problems (Krull et al, 2018).…”
mentioning
confidence: 99%